Dental practice in Europe at the end of the 18th century - Hillam, Christine; Ingenta (Firm : 1998-2007) (Amsterdam ; New York : Rodopi, 2004)
Here is presented for the first time an overview of dental practice and the providers of dental treatment at the close of the eighteenth century in some of the major countries of western Europe and further afield. It draws on previously under-explored primary sources, rigorously referenced, and enables comparison of and contrast within the emergent specialty in rapidly-changing social and political environments. The overall picture challenges conventional wisdom and will be of interest to social as well as to dental and medical historians.
Foreword / David Hillam -- Preface / Christine Hillam -- Contributors / Christine Hillam -- Introduction: Dental Practice in Europe at the End of the 18th Century / Christine Hillam -- Dental Practitioners in France at the End of the Eighteenth Century / Pierre Baron -- Dental Practice in Selected Areas of France / Pierre Baron -- Dental Practice in Paris / Pierre Baron -- France: Discussion / Pierre Baron -- Dentistry in the British Isles / Anne Hargreaves -- Itinerant Dentists and Patent Remedies in the Dutch Republic / Frank Huisman -- Dental Practice in Hungary at the End of the Eighteenth Century / Judit Forrai -- Germany between 1780 and 1810 / Thomas Nickol and Curt Gerhard Lorber -- German Dental Literature around 1800 / Thomas Nickol -- Biographical Sketches of some Dental Practitioners in Germany at the End of the Eighteenth Century / Peter Schröck-Schmidt and Curt Gerhard Lorber -- The Availability of Dental Care in Halle: A Local Study / Thomas Nickol -- French Sources / Christine Hillam -- List of Individuals Offering Dental Treatment in Selected Areas of France, 1785-1800, with their Designation1 and Place and Dates of Practice / Christine Hillam -- A Select Bibliography of the French Authors / Christine Hillam -- List of Individuals Offering Dental Treatment in Britain in the 1790s: (with main centres of activity and approximate dates) / Christine Hillam -- Alphabetical List of German Dental Literature Published Between 1775 and 1820 / Christine Hillam -- Individuals Offering Dental Treatment in Germany Between c.1780 and 1810 / Christine Hillam -- Index / Christine Hillam.
Electronic book available in PDF.
System requirements: world wide web browser, Internet connecticut, realPage viewer or Sdobe Acrobat reader.
Mode of access: world wide web.
Digitized and made available on the world wide web by Ingenta.
Includes bibliographical references (pages 459-466) and index.
eBooks on EBSCOhost
Keywords: Dentistry -- Europe; Dentistry -- History -- 18th century; Medicine -- History -- 18th century; Europe; History of Dentistry; History, 18th Century; Europe; Dentisterie -- Europe; Médecine -- Histoire -- 18e siècle.; Europe; Medicine; Dentistry; Europe; Zahnmedizin; Europa; 1700-1799; History